Clocks at a snail pace: biological rhythms in terrestrial gastropods - Salvador,Rodrigo Brincalepe; Tomotani,Barbara Mizumo (PeerJ, 2024)
Biological rhythms are ubiquitous across the tree of life. Organisms must allocate their activities into moments of the day and of the season that will increase their probability of surviving and reproducing, which is done in the form of daily and annual rhythms. So far, the vast majority of studies on biological rhythms have focused on classical laboratory model species. Still, the use of non-model species is gaining traction, as part of an effort to achieve a more holistic understanding of clock/calendar mechanisms in the “real world” but this requires species that can be studied in both the lab and in nature. Terrestrial gastropods, i.e., land snails and slugs, have the potential to be exciting models for the study of biological rhythms in nature. Therefore, we provide a review of the research on biological rhythms in terrestrial gastropods, with a focus on ecology and evolution. We present the state of the art in the field while giving a historical perspective of the studies, exploring each of the main lineages of terrestrial gastropods. We also point out some interesting directions that future studies could take to fill some of the more urgent gaps in current knowledge. We hope that our contribution will renew interest in this area and spark novel projects.
Keywords: Biological clocks; Daily rhythms; Land snails; Systellommatophora; Stylommatophora; Aestivation; Hibernation; Annual rhythms